2016
DOI: 10.18372/2410-7840.18.10110
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for building cyberattack-generated anomaly detection systems

Abstract: Развитие информационных технологий трансформируется настолько быстро, что классические механизмы защиты не могут оставаться эффективными, а вредоносное программное обеспечение и другие киберугрозы становятся все более распространенными. Поэтому необходимы системы обнаружения вторжений, позволяющие оперативно обнаруживать и предотвращать нарушения безопасности (особенно ранее неизвестных кибератак), характеризующихся нечетко определенными критериями. Известны кортежная модель формирования набора базовых компоне… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The analysis of the complex of technical information protection is considered in [9], the risks of the identifiers tree of state information resources in [10]. In [11], a methodology for constructing systems for detecting anomalies generated by cyber attacks was considered. In [12], there is a methodology for analyzing and assessing the risk of loss of information resources.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the complex of technical information protection is considered in [9], the risks of the identifiers tree of state information resources in [10]. In [11], a methodology for constructing systems for detecting anomalies generated by cyber attacks was considered. In [12], there is a methodology for analyzing and assessing the risk of loss of information resources.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The methodology of adaptive risk assessment systems for the security of information system resources is considered in [14]. The analysis of the proposed methodologies in [8][9][10][11][12][13][14] showed that the authors use only individual components of information resource security, information security, as a rule, do not take into account the relationship between information assets, elements of the information infrastructure of the corresponding computer networks/systems, the possibility of integration and properties of hybridity of threats to security components [15][16][17]. Therefore, the reviewed methodologies will require a radical revision in terms of the creation of a methodological basis for building an information security system in CRES both of the world as a whole and of Ukraine in particular.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%